Evaluation On Tuna Loin Handling As Raw Materials To Improve The Quality Of Frozen Tuna Loin in Ambon - Theresia Dwi Suryaningrum; Diah Ikasari (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2019)
Tuna fishing in Ambon is mostly conducted by small scale fishers using small boats (1.5 GT) and traditional fishing gear. The caught tuna was loined on board and collected at landing post or mini-plant before being sent to an UPI in Ambon. The study was aimed to evaluate the handling of tuna loin at small scale fishers during processing frozen tuna loin product. Two forms of tuna loin i.e skin-on and the skin-less tuna loin, obtained from the fishers in Latuhalat and Tial districts in Ambon and than was stored in ice overnight.  Tuna loin was  sent to Fish Processing Unit  and cleaned from the skin (for skin-on tuna loins) or trimmed (for the skin-less tuna loins). Then, tuna loins were treated with CO, wrapped with styrofoam paper, packed with plastic and incubated in chilling room at 1.12oC for 2 days until the tuna meat color becomes reddish. The tuna loins were then frozen using Air Blast Freezer (temperature of -35oC) for 8 hours. Observations were performed on the physical (temperature) and chemical properties (proximate analysis, pH and TVB), microbial contaminants (TPC, E coli and Salmonella) as well as the sensory properties of tuna loin at each processing steps, starting from   when the tuna loin was landed and handled at the collecting level,   after stored in ice overnight  before CO treatment,  after treated with CO and incubated in chilling room for 2 days before frozen tuna loin products.  The study showed that the existing tuna handling during processing  and  frozen of frozen tuna loins tended to cause quality decrease of the tuna loins. Tuna loins in the form of skin-less produced better quality compared to skin-on tuna loins. The quality decrease of tuna loin occured rapidly during incubation process after treated with CO, showed by the decrease of TVB and organoleptic values as well as the increase of bacterial content. However, the frozen tuna loin products were still meeting the requirements for frozen tuna based on Indonesia National Standard 01.2346-2006.